WORKSHOP MAKET 15 MENIT DI SMA PERMAI: KOREK API DAN KETERBANGUNAN - Nina Carina; Keira Edeline; Jason Christian Adam (Jurnal Serina Abdimas, 2025)
Public knowledge regarding the Architecture study program remains limited. As a discipline predominantly housed under the Faculty of Engineering, Architecture is often perceived as a field strongly associated with technical calculations, while at the same time requiring creativity and drawing skills. Consequently, many high school students assume that proficiency in mathematics and manual drawing is a prerequisite for entering an architecture program. However, recent developments in architectural education in Indonesia—where the discipline is no longer dominated by engineering approaches and where computational design tools increasingly reduce the reliance on manual drawing—remain largely unfamiliar to the wider public, particularly to grade X and XI students at SMA Permai, North Jakarta. In response, the Community Service Team of Universitas Tarumanagara designed an outreach activity to introduce students to basic architectural thinking and practice. Considering the characteristics of Generation Z and the limited time available, the team implemented a “15-Minute Model Workshop.” Using simple wooden matchsticks as the primary material, students were encouraged to collaborate in groups, an essential skill for succeeding in higher architectural education. The workshop further provided opportunities to quickly search for precedents, experiment under time and resource constraints, and make design decisions to produce multiple creative alternatives. Each group concluded with a brief presentation of their work. Through this process, participants gained valuable experiences in teamwork, information seeking, experimentation, creative production, and public presentation—skills that constitute key success factors in architectural education. Ultimately, the 15-Minute Workshop broadened students’ understanding of architecture as a dynamic field of higher education. Pengetahuan Masyarakat mengenai Program Studi Arsitektur masih terbatas. Arsitektur sebagai program studi yang sebagian besar berada di bawah naungan Fakultas Teknik masih dikonotasikan dalam ilmu teknik yang penuh dengan pelajaran hitungan namun disatu sisi dituntut untuk kreatif dan berbakat menggambar. Hal ini membuat banyak siswa SMA mengira bahwa untuk menjadi mahasiswa arsitektur, keahlian menghitung dan menggambar menjadi syarat mutlak. Perubahan dunia pendidikan arsitektur Indonesia yang saat ini tidak lagi didominasi ilmu Teknik serta hadirnya beragam program komputasi desain yang membuat keahlian menggambar manual tidak lagi mutlak, belum banyak diketahui masyarakat luas, khususnya siswa kelas X dan XI di SMA Permai, Jakarta Utara. Tim Pengabdian Kepada Masyarakat Untar berusaha menghadirkan pengetahuan dan pengalaman singkat berarsitektur kepada siswa-siswi SMA Permai. Melalui pemahaman mengenai karakter generasi Z serta adanya batasan waktu yang diberikan, Tim merencanakan dan melaksanakan workshop maket 15 menit. Melalui Workshop 15 menit dengan bahan dasar korek api kayu, siswa-siswi peserta workshop mendapatkan pengalaman bekerjasama dalam kelompok. Bekerjasama dalam kelompok merupakan salah satu syarat keberhasilan dalam menempuh pendidikan tinggi arsitektur. Peserta workshop juga mendapatkan pengalaman mencari preseden secara cepat, bereksperimen dalam keterbatasan waktu dan alat hingga membuat keputusan desain guna menghasilkan beberapa alternatif karya kreatif yang dapat terbangun. Workshop diakhiri dengan presentasi singkat setiap kelompok. Pada akhir workshop peserta mendapatkan pengalaman bekerjasama, mencari informasi, bereksperimen, berkreasi kreatif serta keberanian berpresentasi yang kesemuanya merupakan kunci keberhasilan menjalankan pendidikan tinggi arsitektur. Melalui workshop 15 menit siswa-siswi SMA Permai memiliki pemahaman yang lebih luas mengenai pendidikan tinggi Arsitektur.